How to incorporate CAD/CAM fabrication into a basic design studio? A preliminary framework for the “e-basic design studio” - Chor-Kheng Lim (PARC: Pesquisa em Arquitetura e Construção, 2013)
The objective of this study is to apply the teachings of CAD/CAM fabrication to basic design studios for 1st and 2nd year undergraduate students. Consequently, the study concludes with an “e-basic design studio” framework based on literature analysis and design studio observations, which includes new tectonics thinking and the operation of traditional 2D/3D design tools and CAD/CAM digital tools.